Studi Laju Infiltrasi Pada Lahan Irigasi Gumbasa (Studi Kasus di BGKn 38, 42 dan 51) - Afrianto, B.; Sutapa, I.W.; Hidayat, N.; Herman, R. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2022)
The 2018 earthquake that shook the city of Palu and surrounding areas with the power of 7.4 MW triggered liquefaction in several locations. Earthquakes and liquefaction that occurred caused damage to Gumbasa’s irrigation canals and some paddy fields. This study was conducted at three points in the paddy fields which 2 points located in the Soulowe village and Sidera village, District of Dolo and one is located in the Lolu village, District of Biromaru. This study aims to determine the infiltration rate in the residents’s paddy fields which have not been planted with paddy for a long time. This is because until the data retrieval performed, Gumbasa irrigation network has not functioned and still under repair. Data were collected using a Double Ring Infiltrometer measuring instrument. The results obtained from this study for constant infiltration rate of BGKn 38 = 1.27 cm/hour, BGKn 42 = 1.10 cm/hour and BGKn 51  = 0.75 cm/hour, which all three are classified as a rather slow with a constant infiltration rate ranging from 0.5 to 2 cm/hour. For the difference in fc values, BGKn 38 and BGKn 42 at 0.17 cm/hour and BGKn 42 and BGKn 51 at 0.35 cm/hour, so that BGKn 38 and BGKn 51 is 0.52 cm/hour. Meanwhile, the value of the difference f0 from the three points is BGKn 38 with BGKn 42 at 3.82 cm/hour and BGKn 42 with BGKn 51 at 4.43 cm/hour, and BGKn 38 with BGKn 51 is 0.61 cm/hour.